2021
DOI: 10.1101/2021.08.09.455770
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Role of Low Molecular Weight Fungal Metabolites in Grapevine Trunk Disease Pathogenesis: Eutypa Dieback and Esca

Abstract: Eutypa dieback and Esca are serious grapevine trunk diseases (GTDs) caused by fungal consortia causing large economic losses in vineyards. Depending on the disease the species involved include Eutypa lata, Phaeoacremonium minimum, and Phaeomoniella chlamydospora. There is a need to understand the complex pathogenesis mechanisms used by these fungi to develop treatments for the diseases they cause. Low molecular weight metabolites (LMW) are known to be involved in non-enzymatic oxygen radical generation in fung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…The enzymatic reduction of eutypine gives its corresponding alcohol, eutypinol, which is not toxic to grapevine, suggesting this as a detoxification pathway for eutypine [9]. In addition to eutypine, other phytotoxic compounds are thought to be involved in foliar symptoms [3,97,98]. For instance, Andolfi et al (2011) reported that E. lata produced related secondary metabolites, mainly acetylenic phenols, along with some low-molecular-weight metabolites involved in the chelator-mediated Fenton (CMF) reactions that generate highly damaging reactive hydroxyl radicals, likely inducing necrosis on grapevine wood tissue [3].…”
Section: Biocontrol Of Eutypa Diebackmentioning
confidence: 99%
See 1 more Smart Citation
“…The enzymatic reduction of eutypine gives its corresponding alcohol, eutypinol, which is not toxic to grapevine, suggesting this as a detoxification pathway for eutypine [9]. In addition to eutypine, other phytotoxic compounds are thought to be involved in foliar symptoms [3,97,98]. For instance, Andolfi et al (2011) reported that E. lata produced related secondary metabolites, mainly acetylenic phenols, along with some low-molecular-weight metabolites involved in the chelator-mediated Fenton (CMF) reactions that generate highly damaging reactive hydroxyl radicals, likely inducing necrosis on grapevine wood tissue [3].…”
Section: Biocontrol Of Eutypa Diebackmentioning
confidence: 99%
“…GTDs represent a group of vascular diseases caused by fungi affecting grapevine wood, mainly through pruning wounds, and inhabiting the xylem cells in the woody tissue [ 1 , 2 ]. The colonization of this tissue leads to a decline in the plant host because of a loss of the xylem function and subsequent decrease in hydraulic conductivity, causing significant necrosis and decay with time, which ultimately lead to foliar symptoms and grapevine death [ 3 , 4 , 5 ]. Esca, Botryosphaeria dieback, and Eutypa dieback are the most frequent on mature grapevines; they decrease vineyard longevity, thereby affecting wine quality and causing huge economic losses throughout the viticulture sector [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%